Correlations Amongst Functional and Morphological Attributes and Oxidative Markers of Fresh and Cryopreserved Semen of Gir and Murrah Bulls - Patel, Tapasvi M; Dhami, AJ; Chaudhri, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study was undertaken during the winter season on healthy mature Gir cattle and Murrah buffalo bulls (n=3 each). The semensamples (6 ejaculates/bull, total 36 ejaculates) collected in the morning using artificial vagina were evaluated for routine seminalattributes, including acrosomal and plasma membrane integrity. The samples were then diluted @ 100 million sperm/ml with tris fructoseyolk glycerol extender without and with sericin @ 0.1, 0.25, 0.5 and 1.0% (w/v), filled in French mini-straws, and frozen in LN2 usingbiofreezer as per standard freezing protocol. Straws were thawed in water bath at 37°C for 30 sec and evaluated for post-thaw quality,viz., motility, viability, morphology, acrosome integrity and plasma membrane integrity (HOST). Lipid peroxidation (malondialdehyde -MDA production) and activities of enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx) were assessed as oxidativemarkers in seminal plasma of freshly diluted and frozen-thawed semen samples. Sericn at 0.5% level significantly (p
Keywords: Bovine semen; Correlations; Fresh semen; Frozen-thawed semen; Oxidative markers; Spermatozoal attributes